Vloga hormonov pri nastanku aken in terapevtski pristopi - Haler, Lea (Placebo, 2025)
the internal processes happening within the body, especially at the level of hormonal imbalance. They are particularly pronounced during adolescence, when hormonal changes stimulate increased sebaceous gland activity. They are caused by clogged pores and excessive sebum secretion, leading to inflammation and various forms of acne. In addition to visible skin changes, acne significantly affects emotional wellbeing, causing low self-esteem and related issues. Diagnosis includes a clinical examination and, if necessary, a laboratory analysis of hormones, especially in adult women with signs of hyperandrogenism. The treatment approach is holistic, ranging from topical preparations to systemic therapies, where hormonal treatment plays a key role in women with hormonal imbalance.
Keywords: acne; adolescenca; adolescence; akne; hiperandrogenizem; hormones; Hormoni; hyperandrogenism; inflammation; Mozoljavost; sebum; vnetje